Persepsi Guru terhadap Tantangan Profesionalisme di Tengah Perubahan Kurikulum - Sofia, Siti; Nashrullah, Muhammad Iqbal (Lembaga Yasin AlSys, 2025)
The transition from the 2013 National Curriculum to the Kurikulum Merdeka introduces new challenges for teacher professionalism in Indonesia, particularly in adopting more flexible, differentiated, and project-based learning approaches, as well as managing administrative tasks through digital platforms such as PMM. This study aims to: (1) analyze the challenges to teacher professionalism in adapting to curriculum change; (2) identify teachers’ perceptions of Kurikulum Merdeka implementation; and (3) formulate strategies for strengthening professionalism through reflection and self-development. A qualitative method was employed using a library research approach, analyzing relevant national scholarly articles published over the past ten years. The findings indicate that teachers encounter difficulties in comprehending the philosophy of Kurikulum Merdeka, developing Learning Objective Pathways (Alur Tujuan Pembelajaran), and integrating technology into classroom instruction. Teacher perceptions of the curriculum vary depending on school context, training experience, and institutional support. Teachers who actively participate in learning communities and engage in regular reflection exhibit greater adaptability. Reflective practice has been shown to enhance pedagogical capacity, administrative efficiency, and teachers’ psychosocial resilience. The study concludes that sustained reflection is essential for reinforcing teacher professionalism. In practical terms, teacher development policies should emphasize contextual, collaborative approaches and promote a reflective culture within school environments.